Reactive Oxygen Species Penetrate Persister Cell Membranes of Escherichia coli for Effective Cell Killing - Kawano, Aki; Yamasaki, Ryota; Sakakura, Tatsuya; Takatsuji, Yoshiyuki; Haruyama, Tetsuya; Yoshioka, Yoshie; Ariyoshi, Wataru (Frontiers in Cellular and Infection Microbiology, 2020)
Persister cells are difficult to eliminate since they are tolerant to antibiotic stress. In the present study, using artificially induced Escherichia coli persister cells, we found that reactive oxygen species (ROS) had greater effects on persister cells than on exponential cells. Thus, we aimed to determine which types of ROS could effectively eliminate persister cells and elucidate the mechanisms underlying the effects of these ROS. Ultraviolet (UV) light irradiation can kill persister cells, and bacterial viability is markedly increased by UV shielding. UV induces the production of ROS, which kill bacteria by moving toward the shielded area. Electron spin resonance-based analysis confirmed that hydroxyl radicals are produced by UV irradiation, although singlet oxygen is not produced. These results clearly revealed that ROS sterilizes persister cells more effectively than exponential cells. These ROS do not injure the bacterial cell wall but rather invade the cell, followed by cell killing. Additionally, the sterilization effect on persister cells was increased by exposure to oxygen plasma during UV irradiation. However, vapor conditions decreased persister cell sterilization by reducing the levels of hydroxyl radicals. Our results demonstrate that persister cells strongly resist the effects of antibiotics and starvation stress but are less able to withstand exposure to ROS.